THE USE OF DIORAMAS AS AN INNOVATIVE MEDIA FOR IPAS IN FOURTH GRADE ELEMENTARY SCHOOL - Puji Liana Dewi; Abdul Karim; Sati (Jurnal Cakrawala Pendas, 2026)
Learning outcomes are the primary output of the learning process. Low student achievement is a problem in the learning process. In this study, low achievement is attributed to the fact that instruction is theoretical and monotonous and does not utilize engaging, concrete teaching materials; as a result, students still struggle to understand the material—particularly abstract concepts—which makes learning tedious. This study aims to determine the effects and benefits of using dioramas on the learning outcomes of fourth-grade students at SD Negeri 1 Kasugengan Kidul. The research method used was a quantitative experimental study with a single-group pre-experimental design involving pre- and post-tests. The study population consisted of all students at SD Negeri 1 Kasugengan Kidul. The sampling technique used was non-probabilistic sampling, specifically a subjective sampling technique in which the sample was selected based on specific considerations. The sample consisted of 21 students. Data were collected through academic achievement tests, observations, and documentation. The research instruments included pre-test/post-test performance assessments consisting of five essay questions, a learning module observation sheet, teacher performance observations, affective observations, and student psychomotor observations. The results showed that the average score on the pre-test, which was initially 41.19, increased to 83.57 on the post-test. The normality test results indicated a normal distribution. Data analysis using the N-gain score test yielded a value of 0.7314, which falls into the “high” category, with an N-gain percentage of 73.1415%, classified as “effective.” Based on the hypothesis test using a t-test on paired samples, the significance value was < 0.001 < 0.05, with a value greater than the critical value, namely 27.051 > 2.086; thus, H₀ was rejected and H₁ was accepted. This means that this study demonstrates a significant effect of the diorama medium on the learning outcomes of fourth-grade students at SD Negeri 1 Kasugengan Kidul.